1986
DOI: 10.1073/pnas.83.12.4350
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA differentiation in North Atlantic eels: Population genetic consequences of an unusual life history pattern

Abstract: A survey of restriction site polymorphism in the mitociibndrial DNA (mtDNA) of the American eel Anguilla rostrata showed no genetic divergence among samples from a 4000-km stretch of North America coastline. Lack of geographic differentiation in mtDNA over such a large area contrasts sharply with results for terrestrial and freshwater vertebrates and is most likely attributable to the extraordinary life history of these catadromous fishes, which involves perhaps a single spawning population in the western trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(137 citation statements)
references
References 12 publications
8
128
1
Order By: Relevance
“…This hypothesis is supported by early genetic studies using allozyme and mitochondrial DNA markers (DeLigny & Pantelouris 1973;Comparini et al 1977;Comparini & Rodinò 1980;Yahyaoui et al 1983;Lintas et al 1998), which found no evidence for a spatial genetic structure. Similar results were obtained for the American eel (A. rostrata; Avise et al 1986) and the Japanese eel (A. japonica; Sang et al 1994), with the exception of clinal allozyme variation putatively imposed by selection (Williams et al 1973;Koehn & Williams 1978;Chan et al 1997). Therefore, panmixia in the European eel was widely accepted until three independent genetic studies recently reported evidence for a weak but significant population structure (Daemen et al 2001;Wirth & Bernatchez 2001;Maes & Volckaert 2002), with two of them finding evidence for isolation-by-distance (IBD) (Wirth & Bernatchez 2001;Maes & Volckaert 2002).…”
Section: Introductionsupporting
confidence: 83%
“…This hypothesis is supported by early genetic studies using allozyme and mitochondrial DNA markers (DeLigny & Pantelouris 1973;Comparini et al 1977;Comparini & Rodinò 1980;Yahyaoui et al 1983;Lintas et al 1998), which found no evidence for a spatial genetic structure. Similar results were obtained for the American eel (A. rostrata; Avise et al 1986) and the Japanese eel (A. japonica; Sang et al 1994), with the exception of clinal allozyme variation putatively imposed by selection (Williams et al 1973;Koehn & Williams 1978;Chan et al 1997). Therefore, panmixia in the European eel was widely accepted until three independent genetic studies recently reported evidence for a weak but significant population structure (Daemen et al 2001;Wirth & Bernatchez 2001;Maes & Volckaert 2002), with two of them finding evidence for isolation-by-distance (IBD) (Wirth & Bernatchez 2001;Maes & Volckaert 2002).…”
Section: Introductionsupporting
confidence: 83%
“…Molecular studies in both species have demonstrated that they are panmictic Côté et al, 2013). Remarkably, although mitochondrial DNA lineages of the two species are reciprocally monophyletic (Avise et al, 1986), low differentation is found at microsatellite loci, with F ST values of 0.055 and 0.018 reported in previous studies (Mank and Avise, 2003;Wirth and Bernatchez, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…We know, however, that species and populations vary in tolerance, plasticity, adaptive potential, and biotic interactions, all of which mediate responses to environmental variation (15)(16)(17) and ultimately dictate the degree of spatial and temporal concordance in genetic structure. The early definition of phylogeographic response categories acknowledged that differences could stem from species-specific traits such as dispersal potential and life history (1,18). Not surprisingly, species that are exceptions to regional phylogeographic patterns have been identified in most, if not all, phylogeographic hotspots, precluding generalizations and challenging expectations for shared causes of organismal diversification.…”
Section: Species-specific Traits and Idiosyncratic Phylogeographic Pamentioning
confidence: 99%